The effect of fuel additives on performance and emission of four stroke engine / Junaidah Md Saad - Md Saad, Junaidah (2010)
This thesis investigates the effect of using palm oil base on four stroke engine performance and exhaust emission, A four stroke, four cylinder SI engine (type Myvi, DVVT DOHC) was used for conducting this study. This investigation focuses on the comparison of performances of an internal combustion engine fitted with the fuel additive. Performance tests were conducted for, fuel consumption, engine torque and engine power, while exhaust emissions were analyzed for carbon monoxide (CO), carbon dioxide (CO2), oxygen (O2) and unburned hydrocarbons (HC), and variable engine speed ranging from 2000 to 6000 rpm. The engine performances were tested on a chassis dynamometer. The peak power and torque curve were recorded. A flue gas analyzer was used in the gaseous emissions tests to measure the gaseous emissions such as CO, CO2, O2 and HC produced in the exhaust gas. The test was done at three different engine speeds, which are idling speed, 2000 rpm and 3000 rpm. Lastly, for the fuel consumption test, the car was filled with 100 ml of fuel. The test was done for a constant speed of 50 km/h and the distance covered by the car before the engine died was measured. The results showed that the effect of the adding fuel addictive gives more power and fuel efficient compared to the petrol.